Return to the System within 30 Days of Discharge after Pediatric Appendectomy. Issue 7 (July 2016) - Short, Heather L.; Sarda, Samir; Heiss, Kurt F.; Chern, Joshua J.; Raval, Mehul V.
Postprocedural revisits, readmissions, and reoperations are commonly tracked quality metrics and have reimbursement and hospital-level comparison implications. Our purpose was to document these rates after pediatric appendectomy and to identify patient factors related to these metrics. This study included 3756 appendectomies performed at a single institution from 2009 to 2013. Data were prospectively collected and clinical events within 30 days of discharge were analyzed. Regression models identified factors associated with each metric. There were 328 returns to the emergency department (8.7%), 128 readmissions (3.4%), and 41 reoperations (1.0%). The main source of read-mission was the emergency department (n = 118, 92%). Nearly two-thirds of readmissions were nonoperative (n = 87, 68%) and 12.5 per cent of readmissions were not related to the index appendectomy. Factors associated with readmission include procedure length >70 minutes [odds ratio (OR) 1.89, P = 0.043] and failed nonoperative management of perforated appendicitis (OR 2.97, P = 0.041). The most common indication for reoperation was intra-abdominal abscess (n = 20, 49%), 55 per cent of which were managed with image-guided drainage. In conclusion, although 30-day revisit, read-mission, and reoperation rates after appendectomy are low, there are opportunities for improvement. Furthermore, many 30-day readmissions are not related to the index procedure and must be clearly identified to avoid inaccuracies with reimbursement and quality rankings.